The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0361-3682(03)00033-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance implications of strategic performance measurement in financial services firms

Abstract: This study examines the relation between measurement system satisfaction, economic performance, and two general approaches to strategic performance measurement: greater measurement diversity and improved alignment with firm strategy and value drivers. We find consistent evidence that firms making more extensive use of a broad set of financial and (particularly) non-financial measures than firms with similar strategies or value drivers have higher measurement system satisfaction and stock market returns. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
558
2
43

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 822 publications
(690 citation statements)
references
References 29 publications
34
558
2
43
Order By: Relevance
“…In fact, there is a significant number of studies supporting the beneficial effects of PMS in the business performance, whether being financial or non-financial performance (e.g. Davis & Albright, 2004;Hoque & James, 2000;Ittner et al, 2003), as well as the beneficial effects on the managers' perceptions of performance (e.g. Chenhall, 2005;Hoque & James, 2000;Lee & Yang, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is a significant number of studies supporting the beneficial effects of PMS in the business performance, whether being financial or non-financial performance (e.g. Davis & Albright, 2004;Hoque & James, 2000;Ittner et al, 2003), as well as the beneficial effects on the managers' perceptions of performance (e.g. Chenhall, 2005;Hoque & James, 2000;Lee & Yang, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, information that a PMS provides to managers may be used to remove uncertainties in the decision-making processes, evaluate processes and the consequences of past decisions as well as possibly suggesting corrective measures and improvements in organizational learning (Grafton, Lilis & Widener, 2010;Pavlov & Bourne, 2011). Several researchers, such as Chenhall (2005), Ittner, Larcker and Randall (2003), and Kaplan and Norton (1996; state that an integrative PMS helps organizations to achieve strategic competitiveness, not only by aligning internal processes with the long-term strategic goals, linking them to short-term actions, but also by developing organizational learning. For instance, the BSC (Kaplan & Norton, 1992;1996; provides a framework for managing the implementation of strategies, containing a wide set of performance measures (KPIs), customer relations, internal business processes, and an organization's learning and growth activities that allow, at the same time, to deal with changes in the company's competitive market and technological environments.…”
Section: Introductionmentioning
confidence: 99%
“…The cause and effect in BSC was found not based on the statistical causality testing but relied on logic assumption and identification of relationship is merely depends on user's belief [11]. Results from previous studies found that the relationships between customer satisfaction and loyalty to revenue in BSC were not represented by causal relationship but based on logical relationships instead [3,4]. Earlier researchers were proposed to conduct a causality test on the relationship in BSC.…”
Section: Balanced Scorecard (Bsc) and Causality In Bscmentioning
confidence: 99%
“…Earlier researchers were proposed to conduct a causality test on the relationship in BSC. This concern was very important as only 23% of firms built and checked their causal models [4]. It was found that the relationships between employee engagement to revenue and vice versa showed only correlation and not causation [12].…”
Section: Balanced Scorecard (Bsc) and Causality In Bscmentioning
confidence: 99%
See 1 more Smart Citation